Historical dictionary of Syria - Commins, David Dean; Lesch, David W. (Historical dictionaries of Asia, Oceania, and the Middle East., 2014)
This third edition covers the recent events in Syria and the history that led up to these events through a chronology, an introductory essay, and an extensive bibliography. The cross-referenced dictionary section has more than 500 entries on significant people, places, events, political parties, institutions, literature, music, and arts.